2020
DOI: 10.1111/jcmm.15039
|View full text |Cite
|
Sign up to set email alerts
|

The rapidly advancing Class 2 CRISPR‐Cas technologies: A customizable toolbox for molecular manipulations

Abstract: The CRISPR‐Cas technologies derived from bacterial and archaeal adaptive immune systems have emerged as a series of groundbreaking nucleic acid‐guided gene editing tools, ultimately standing out among several engineered nucleases because of their high efficiency, sequence‐specific targeting, ease of programming and versatility. Facilitated by the advancement across multiple disciplines such as bioinformatics, structural biology and high‐throughput sequencing, the discoveries and engineering of various innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 152 publications
(375 reference statements)
0
34
0
Order By: Relevance
“…CRISPR-Cas systems are divided into different types depending on their cas genes and their mode of CRISPR interference, which in turn has given rise to an expanding and broad range of novel genetic engineering tools ( 7, 38, 39 ). The type I-D CRISPR-Cas system appears to be a hybrid of type I and type III systems, yet the type I-D Cascade, involved in binding target nucleic acids, remained uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-Cas systems are divided into different types depending on their cas genes and their mode of CRISPR interference, which in turn has given rise to an expanding and broad range of novel genetic engineering tools ( 7, 38, 39 ). The type I-D CRISPR-Cas system appears to be a hybrid of type I and type III systems, yet the type I-D Cascade, involved in binding target nucleic acids, remained uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Cas12 has emerged as an alternative for Cas9 due to its distinct features, such as the ability to target T-rich motifs and no need for trans-activating crRNA. To this date, various subtypes of Cas12 proteins have been discovered ( Wang et al, 2020a ). Table 2 summarizes various subtypes of Cas12 proteins and their characteristics.…”
Section: Cas12-based Sars-cov-2 Detectionmentioning
confidence: 99%
“…The type V proteins members possess the RuvC nuclease domain instead HNH domain to identify the site-specific T-rich PAM (5′) sequence just upstream to target region. In addition, Cas12 nucleases built staggered DSBs distal to PAM sequence unlike to Cas9 that helped to generate the unique knock-in strategies for genome editing through HNEJ mechanism [ 78 ].…”
Section: Other Cas Family Membersmentioning
confidence: 99%
“…These two proteins also carried some unique features, unlike Cas9 like these proteins cleaved the ssRNA instead of DNA because they have no catalytical DNA domain. Recently, studies stated that Cas13 proteins possess two identified highly conserved prokaryotic and eukaryotic nucleotide-binding domains containing specific RNA cleavage site [ 78 , 83 ]. Zhao et al [ 84 ] stated that bacterial Cas13a and CRISPR-RNA (crRNA) showed the successful knockout effects in mutant KRAS mRNA expression with the knockout efficiency of about 94%.…”
Section: Other Cas Family Membersmentioning
confidence: 99%